Mucocutaneous changes in tuberous sclerosis complex: A clinical profile of 27 Indian patients - Ghosh Sudip; Bandyopadhyay Debabrata; Chatterjee Gobinda; Ghosh Arghyaprasun; Sarkar Sharmila; Sarkar Somenath (Indian Journal of Dermatology, 2009)
Background: Tuberous sclerosis complex (TSC) is an autosomal dominant neurocutaneous disease resulting in a wide array of clinical manifestations, primarily affecting the skin and central nervous system. Mucocutaneous features play a very important role in the recognition of this syndrome. Aims: To review the prevalence and patterns of cutaneous manifestations in tuberous sclerosis, in a group of patients from eastern India. Methods: Observational clinical study on twenty-seven consecutive patients of tuberous sclerosis collected during a period of four years. Results: Most were between 10-20 years of age; the male to female ratio was 2:1. Family history was found in two-thirds. The classical triad of tuberous sclerosis was present in only nine (33.3%) patients. Adenoma sebaceum was the most common cutaneous feature (100%), followed by hypomelanotic macules (92.6%), connective tissue nevi (66.6%), and Koenen′s tumors (33.3%). Oral mucosal fibromas were seen in six (22.22%) patients. Fibromatous plaque over forehead and scalp was seen in three patients. Limitation of the study was small size of study sample. Conclusion: Prominent mucocutaneous changes are extremely common manifestation of TSC, which may provide crucial diagnostic clues for primary care physicians.